2021
DOI: 10.1002/jpen.2287
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition challenges of cancer cachexia

Abstract: Cancer cachexia, or progressive weight loss, often despite adequate nutrition contributes greatly to cancer morbidity and mortality. Cachexia is metabolically distinct from starvation or protein malnutrition, although many patients with cancer and cachexia exhibit lowered appetite and food consumption. Tumors affect neural mechanisms that regulate appetite and energy expenditure, while promoting wasting of peripheral tissues via catabolism of cardiac and skeletal muscle, adipose, and bone.These multimodal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 125 publications
(225 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, with no validated cachexia screening tool readily available for clinicians in oncology care and a lack of consistent malnutrition screening, there are significant gaps in detection and management of the syndrome for many patients. 16 Among the cachexia academic community, there is significant enthusiasm for expanding awareness about cancer cachexia. Extending knowledge to primary care, community oncologists, patients, caregivers, and advocates is key to supporting the development of novel therapies, integration of supportive care, and implementation of care pathways that can successfully address the aspects of cancer cachexia most meaningful to the patient experience.…”
Section: Cliniciansmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, with no validated cachexia screening tool readily available for clinicians in oncology care and a lack of consistent malnutrition screening, there are significant gaps in detection and management of the syndrome for many patients. 16 Among the cachexia academic community, there is significant enthusiasm for expanding awareness about cancer cachexia. Extending knowledge to primary care, community oncologists, patients, caregivers, and advocates is key to supporting the development of novel therapies, integration of supportive care, and implementation of care pathways that can successfully address the aspects of cancer cachexia most meaningful to the patient experience.…”
Section: Cliniciansmentioning
confidence: 99%
“…It is further characterized by dysregulation of host metabolic processes at the cellular and molecular level, including mitochondrial dysfunction, glucose dysmetabolism, and unbalanced lipolysis and proteolysis 14,15 . While it is unlikely that a single agent will treat all aspects of this syndrome, recent cachexia research has identified specific biological, endocrine, and immune mechanisms that precipitate loss of body weight, skeletal muscle, appetite, and physical function 16 . For example, factors produced by the tumour and by the host, including inflammatory cytokines, exosomes, small molecules, and microRNAs, signal on distant tissues to suppress food intake and induce catabolism of fat and muscle.…”
Section: The Problem Of Cancer Cachexiamentioning
confidence: 99%
See 3 more Smart Citations